Proposed upgrading and new design for Trekker Lodge Hostel at 1-1 Jalan Angsoka Off Jalan Nagasari, Bukit Bintang 50200 Kuala Lumpur / Siti Nur'ain Mat Isa - Mat Isa, Siti Nur'ain (2008)
Backpacking is a term that has historically been used to denote a form of low-cost, independent international travel. Terms such as independent travel and or budget travel are often used interchangeably with backpacking. The factors that traditionally differentiate backpacking from other forms of tourism include but are not limited to the following such as, use of public transport as a means of travel, preference of youth hostels to traditional hotels, length of the trip vs. conventional vacations, use of a backpack, an interest in meeting the locals as well as seeing the sights. Upgrading and new design is proposed for Trekker Lodge Hostel sdn.bhd at Jalan Angsoka, Kuala Lumpur. The objectives of this project are to design a more systematic and unique planning in order to emerge with a suitable image and mission for this hostel. Methodology applied to run the researches are divided into three phases includes the first phase which is scope of research, client, site proposal and scope of work. Phase two includes three case studies, site and also building analysis. Last phase includes info compilation, analysis, and critique. Spontaneous desires is the concept that being proposed in this project. It shows that backpackers usually travel without properly organize and planning, it is a desire for them to travel in an independence way. From this concept the character of backpackers is showed and it will lead to the design process. Modern minimalism is the style that been choose for this project.